P757 Long-term effectiveness and safety of adalimumab based on Crohn's disease duration: Results from the PYRAMID registry. (16th January 2018) - Loftus Jr, E V; Reinisch, W; Panaccione, R; Berg, S; Bereswill, M; Kalabic, J; Skup, M; Petersson, J; Robinson, A M; D'Haens, G
Abstract: Background: PYRAMID was a non-interventional, uncontrolled, multinational registry of adult patients with Crohn's disease (CD) assessing the long-term safety and effectiveness of adalimumab (ADA; Humira®) in clinical practice. In these analyses, the relationship between CD duration at registry enrolment (baseline [BL]) and treatment outcomes was evaluated in ADA-naïve patients at BL. Methods: Adults (≥(dults [BL]) amoderate-to-severe CD newly prescribed or already receiving ADA were followed for ≤6 years. Effectiveness was evaluated in ADA-naïve patients with ≥1 ADA dose and ≥1 post-enrolment measurement using the Harvey-Bradshaw Index (HBI), Short Inflammatory Bowel Disease Questionnaire (SIBDQ) and Work Productivity and Activity Impairment (WPAI) questionnaire. Data were summarised descriptively as observed; change from BL values was calculated for patients with available values at BL and yearly visits, irrespective of receiving ADA at assessment time, and stratified by BL CD duration (<2, 2 to <5, 5 to <10, and ≥10 years). Adverse events (AEs) were analysed in ADA-naïve patients by CD duration at BL; treatment-emergent AE rates (AEs occurring from BL through 70 days after last ADA dose in registry) were assessed as events per 100 patient-years (E/100 PYs) of registry ADA exposure. Results: Of 5025 registry patients evaluated, 2057 (40.9%) were ADA-naïve at BL. BL CD duration was available for 1980 ADA-naïve patients (<2 years, n = 373; 2–<5 years, n = 334; 5–<10 years, n = 512; ≥10 years, n = 761). Mean total HBI and SIBDQ scores improved from BL in all subgroups at year 1 and these improvements were maintained, with numerically similar improvements across subgroups (Table 1). Mean WPAI subscores improved in all subgroups from BL to year 1 and remained mostly stable through year 6; numerically greater improvements were seen in patients with CD duration <5 vs. ≥5 years. Improvements in SIBDQ (all time points) and WPAI (nearly all time points) scores were clinically meaningful. Overall rates of any AE were generally similar across subgroups, as were rates of infection (7.4–9.0 E/100 PYs) and serious infection (4.4–6.4 E/100 PYs). Conclusions: Initiation of ADA treatment improved patient-reported quality of life and work-related activities in adults with CD. These improvements were maintained for up to 6 years across CD duration subgroups through registry participation. The safety profile for ADA-naïve patients was generally similar across subgroups and comparable with safety data previously reported for the overall registry population.